Identifikasi Prinsip Ekowisata Pada Pengembangan Desa Wisata Cibeusi, Kabupaten Subang - Doni Riswandi; Gina Puspitasari Rochman (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. The variety of potentials owned by Cibeusi Village makes a high selling point for the tourism sector. Cibeusi Village has abundant natural and cultural potential. This potential can be used as a tourist attraction for the development of tourist villages. In addition, the development of tourism in Cibeusi Village, on the other hand, is the conversion of agricultural land into tourism activities such as stalls, recreation areas and lodging or the influence of tourists that damage environmental sustainability. On the other hand, Cibeusi Village has a wealth of biological resources in the form of flora and fauna and natural beauty due to there being tours and there are also resources that must be protected and preserved in their beauty. Thus, it is necessary to study the identification of ecotourism principles, from the description of the problem raises research questions in Cibeusi Village, namely "To what extent are ecotourism principles applied to tourism activities in Cibeusi Tourism Village?" The purpose of this research is to identify ecotourism principles in tourism activities in Cibeusi Village. The approach method used is descriptive qualitative method while the analytical method used is content analysis where the researcher proceeds from documents such as interview transcripts, news media and articles as well as direct observation to Cibeusi Village. In this study, using combined principles that have been adjusted to the conditions in Cibeusi Village itself, the results of the combined principles of the experts produced six principles which will be used as the basis for the ecotourism aspect. The results of the identification of tourism activities in Cibeusi Village with ecotourism principles based on ecotourism principles in Cibeusi Village only fulfill 4 of the 6 principles, the results of this study are expected as recommendations to the management and government of Cibeusi Village. Abstrak. Beragamnya potensi yang dimiliki Desa Cibeusi menjadikan nilai jual yang tinggi bagi sektor pariwisata. Desa Cibeusi mempunyai potensi alam dan budaya yang berlimpah. Potensi tersebut bisa dijadikan daya tarik wisata untuk pengembangan desa wisata. Selain itu, Berkembangnya wisata di Desa Cibeusi disisi lain ada alih fungsi lahan pertanian menjadi kegiatan wisata seperti warung, tempat rekreasi dan penginapan atau pengaruh wisatawan yang merusak kelestarian lingkungan disisi lain juga Desa Cibeusi memiliki kekayaan sumber daya hayati berupa flora dan fauna serta keindahan alamnya dikarenakan ada wisatanya dan ada juga sumber daya yang harus dilindungi dan dilestarikan keasriannya. Dengan demikian, perlu dilakukan kajian identifikasi prinsip-prinsip ekowisata, dari uraian permasalahan memunculkan pertanyaan penelitian yang ada di Desa Cibeusi, yaitu “Sejauh mana prinsip-prinsip ekowisata di aplikasikan pada kegiatan wisata di Desa Wisata Cibeusi?” Tujuan diadakannya penelitian ini adalah untuk mengidentifikasi prinsip-prinsip ekowisata pada kegiatan wisata di Desa Cibeusi. Metode pendekatan yang digunakan adalah metode deskriptif kualitatif sedangkan metode analisis yang digunakan adalah analisis isi dimana peneliti berproses dari dokumen seperti transkrip wawancara, media berita dan artikel serta observasi langsung ke Desa Cibeusi. Pada penelitian ini dari menggunakan prinsip gabungan yang telah disesuaikan dengan kondisi di Desa Cibeusi itu sendiri, hasil dari gabungan prinsip para ahli dikeluarkan enam prinsip yang akan dijadikan dasar untuk aspek ekowisata. Didapatkan hasil identifikasi kegiatan wisata di Desa Cibeusi dengan prinsip ekowisata berdasarkan prinsip-prinsip ekowisata Di Desa Cibeusi hanya memenuhi 4 dari 6 prinsip, hasil dari penelitian ini diharapkan sebagai rekomendasi kepada pihak pengelola maupun pemerintah Desa Cibeusi.